Lubrication effect of metal-on-metal in hip joint replacement - Mohd. Suri, Mohd. Syafiq (2014)
The use of hard-on-hard material is one of alternative methods to replace the soft-on-soft or soft-on-hard material which has long been used in hip joint replacement. The common type of hard-on-hard material used in hip joint replacement is metal-on-metal. However, the metal-on-metal hip implants produce the small wear particle as a result of attrition of the contact surface between femoral head and acetabulum cup. Therefore, the lubrication performance between the surface of the femoral head and acetabulum cup is essential to reduce wear particle. The objective of this study was to determine the effect of lubrication on metal-on-metal hip joint replacement. Two types of contact analysis were performed, without and with lubrication. In the contact analysis of without lubrication, the maximum contact pressure was 32.887 MPa while lubrication contact analysis, maximum contact pressure was lower. It was occurred because between the surface of femoral head and acetabulum cup has full fluid film lubrication. This causes the wear that produced by metal-on-metal hip joint implants can be reduced because an effective lubricant film is able to reduce wear significantly. In addition, this study focused on the design parameters, radial clearance and femoral head size. It was found that the maximum contact pressure increased when the radial clearance also increased and the maximum contact pressure decreased when the femoral head size increased.